The Intersection of Blockchain Technology and Data Security in e-Business - Kostopoulos, Nikos; Antonopoulou, Hera (Technium Business and Management, 2024)
This paper investigates the integration of blockchain technology and data security within an e-business context, articulating the transformative potential of this integration across various key sectors: financial transactions, supply chain operations, digital healthcare, and product authenticity verification. Other important attributes of blockchain, such as decentralization, immutability, and transparency, coupled with powerful security measures, are explored. This indicates the importance of ensuring data security in e-business, especially against cyber threats and insider threats. This paper therefore will explore specific blockchain applications in e-business, focusing especially on smart contracts, supply chain management, and data security. It also accepts challenges, including high development costs and integration problems, but it highlights opportunities according to potential operational efficiencies and overall improvement in transparency. Convergence of blockchain with AI and machine learning is discussed as part of future trends, which sets higher demand for continued research and development to maximize the benefits while at the same time mitigating the risks linked to blockchain technology in e-business. The references cited provide an essential overview of the current research landscape, which spans various digital technologies and their implications in multiple domains.